African sovereign defaults and the common framework: Divergent Chinese interests grant Western countries a "consumer surplus" - Eckhardt Bode (Kiel Institute for the World Economy (IfW Kiel), 2024)
China has become a major player in sovereign lending towards Africa during the past two decades but has recently been faced with increasing defaults. A new African debt crisis is looming. • Differences in the motives of sovereign lending between China and Western creditor countries contribute to preventing effective global sovereign debt management under the "Common Framework for Debt Treatment" in this looming African debt crisis. Chinese lending during the past two decades was motivated primarily by its own economic interests while most of the Western countries' lending appears to be at odds with their self-interests but is not yet well-understood. • Debt settlements under the Common Framework that involve China are less generous than past settlements with the Paris Club alone. This is an obstacle to a rapid and sustainable economic recovery of financially distressed African countries. • Western countries derive a kind of "consumer surplus" from the agreements under the Common Framework because they are prepared to make greater concessions than China. They could transfer this hypothetical surplus as additional (conditional) Official Development Assistance to the defaulted African countries to alleviate social hardship. – – China hat sich in den letzten zwei Jahrzehnten zu einem wichtigen Akteur bei der Vergabe von Staatskrediten an Afrika entwickelt, sah sich aber in letzter Zeit mit zunehmenden Zahlungsausfällen konfrontiert. Eine neue afrikanische Schuldenkrise zeichnet sich ab. • Unterschiede in den Motiven für die Kreditvergabe zwischen China und westlichen Gläubigerländern tragen dazu bei, dass in dieser sich abzeichnenden afrikanischen Schuldenkrise ein wirksames globales Staatsschuldenmanagement gemäß dem "Common Framework for Debt Treatment" verhindert wird. Die chinesische Kreditvergabe war in den vergangenen zwei Jahrzehnten in erster Linie durch eigene wirtschaftliche Interessen motiviert. Die Motive der Kreditvergabe der westlichen Länder scheinen deren wirtschaftliche Interessen dagegen zu widersprechen, sind aber noch weitgehend unerforscht. • Umschuldungen unter dem Common Framework unter Beteiligung Chinas sind weniger großzügig als frühere Regelungen mit dem Pariser Club allein. Dies ist ein Hindernis für eine rasche und nachhaltige wirtschaftliche Erholung der finanziell angeschlagenen afrikanischen Länder. • Die westlichen Länder erzielen aus den Umschuldungen unter dem Common Framework eine Art "Konsumentenrente", weil sie zu größeren Zugeständnissen bereit sind als China. Sie könnten diesen hypothetischen Ertrag als zusätzliche (bedingte) öffentliche Entwicklungshilfe an die insolventen afrikanischen Länder weiterleiten, um soziale Härten zu mildern."
Keywords: 330; Sovereign Debt; Africa; Motives of Lending; China; Western Countries; CommonFramework; Consumer Surplus; Staatsverschuldung; Afrika; Motive der Kreditvergabe; China; westliche Länder; Common Framework; Konsumentenrente